Assessment of Mediterranean Citrus Peel Flavonoids and Their Antioxidant Capacity Using an Innovative UV-Vis Spectrophotometric Approach - Rosario Mare; Roberta Pujia; Samantha Maurotti; Simona Greco; Antonio Cardamone; Anna Rita Coppoletta; Sonia Bonacci; Antonio Procopio; Arturo Pujia (Plants, 2023)
Citrus fruits exert various beneficial health effects due to the large amount of polyphenols they contain. Citrus peels, often considered food waste, contain several health-promoting polyphenols. Among these, flavonoids have long been quantified through colorimetric assays which, if not adequately applied, can lead to conflicting results. Flavonoids possess strong antioxidant properties and can decrease circulating free radicals, thereby reducing oxidative stress phenomena. Quantifying flavonoids and properly estimating their antioxidant capacity allows us to predict plausible beneficial effects of citrus fruits on human health. The aim of this research was to analyze the advantageous phenolic compounds found in the peels of citrus fruits commonly found in the Mediterranean region. The objective was to measure their antioxidant capacity and ability to neutralize free radicals. To achieve this purpose, UV-visible spectrophotometric analyses, liquid chromatography (LC) and Electron Paramagnetic Spectroscopy (EPR) were utilized and compared, finally suggesting an innovative approach for assessing the overall flavonoid content by the nitrite-aluminum assay. HPLC data demonstrated that hesperidin was the most abundant flavonoid in all peel extracts except for orange peels, in which naringin was the predominant flavonoid. The total flavonoid content was greater than 1.3 mg/mL in all extracts, with tangerine and orange yielding the best results. Citrus peel polyphenols exerted strong antioxidant and free radical scavenging effects, inhibiting up to 75% of the free radicals used as reference in the EPR analyses.